Evaluación del efecto de bases catiónicas sobre tela tipo algodón para la producción de un suavizante en industrias químicas Saint Germain Ltda. (2017)
The project was focused on finding the combination of components that met the company's requirements in terms of quality and competitiveness. Secondly, the best-selling softeners in the current market were determined through a survey of 100 people to identify the properties of each one of them and according to these results the softener project guide was chosen.